Penyuluhan hukum: Etika bermedia sosial bagi siswa SMK Tarbiyah Islamiyah Deli Serdang - Arni Meriah Zega; Muhammad Rizky Kurniawan; Adam Siddik Pratama Nasution; Leni Indrayani; Junaidi Lubis (Penamas: Journal of Community Service, 2026)
The abuse of social media such as Facebook, Tik-Tok, Instagram and other social media among teenagers is currently increasing to the stage of addiction, such as high rates of cyberbullying, the spread of false information, and a decline in morale among high school students. The main challenge faced by the partner, SMK Tarbiyah Islamiyah, is the lack of students' legal understanding of ethics in communicating in cyberspace. This community service program aims to provide legal information related to the ethics of using social media based on the Electronic Information and Transaction Law. The implementation of the activity was carried out through interactive legal counseling, which included lectures, group discussions, and simulation case studies on digital ethics violations. The results of this activity showed a significant increase in student understanding, where before this event only 40% of students understood about the legal aspects of social media, and that number jumped to 85% after counseling. Students are now more aware of the importance of filtering content and understanding the legal risks of each post. The conclusion of this activity is that regular legal counseling is very effective in forming responsible attitudes of adolescents on social media, as well as a preventive measure against cybercrime in the school environment.